Road Transport Vehicles for Hauling Uncomminuted Forest Energy Products in Sweden - Reza Mortazavi; Jerry Johansson (International Journal of Forestry Research)
Forestry residues as a renewable energy source are becoming increasingly competitive to fossil fuels. An important issue, however, is effective transportation solutions for this type of material. In this paper we describe and discuss several alternative vehicle systems which have been used in Sweden. We describe and discuss a specialized vehicle for the transportation of loose residues, bundled residues, and tree sections; a specialized stump hauling vehicle; a recently developed vehicle for the transportation of bundled residues; a container system vehicle for stump transportation. All these different machineries have their merits and shortcomings depending on the type of forest energy product.